Determinant Factors Related to the Event of Dengue Hemorrhagic Fever (DHF) in the Work Area of Payung Sekaki Health Center, Pekanbaru Regency - Chitra Dwi Ananda Putri; Buchari Lapau; Agus Alamsyah (Science Midwifery, 2022)
Dengue hemorrhagic fever (DHF) or dengue hemorrhagic fever (DHF) is currently one of the public health problems in Pekanbaru, Riau. The research design is an Unmatched Case Control Study. The case population is all DHF sufferers from 2019-2021, totaling 194 people and the control population is all non-DHF cases in the same period when DHF occurred in 2019-2-2021, totaling 7,624 people. The number of samples is 180 cases and 180 controls. Data were analyzed by univariate, bivariate and multivariate. The results of multivariate analysis, the most influential variables were the habit of hanging clothes (95% CI = 2,970-8,557), the use of repellents during the day (95% CI = 2,272-6,307), knowledge about dengue transmission (95% CI = 2,108-5,892), presence of larvae (CI 95% = 1.716-4.760), sleep during the day (95% CI = 1.699-4.699). The determinant factors related to the incidence of Dengue Hemorrhagic Fever (DHF ) in the Working Area of the Payung Sekaki Health Center are the presence of larvae, daytime sleep habits, hanging clothes habits, daytime use of repellants and knowledge of dengue transmission. While mosquito repellent plants, education, age and gender. It is recommended that the Health Center conduct health education so that people do not hang clothes that have been used, use repellents during the day, do 3M (closing water reservoirs, draining bathtubs, burying), not sleeping during the day and if sleeping during the day need to use tools or mosquito repellent.